Estimation of Tabriz population based on exponential and logistic growth models for water scarcity analysis - Saeed Imani; Yagob Dinpashoh; Esmaeil Asadi; Ahmad Fakheri Fard (Journal of Applied Research in Water and Wastewater)
According to most opinions of researchers, an increase in the population creates many restrictions in relation to water supply in the cities. Because an increase in the population causes climate change, water consumption in the sewage sector, lack of water infrastructure and rising demand for food production. Therefore, accurate planning is needed to predict population numbers in the future years. Therefore, in this research, a specific mathematical equation is introduced for predicting the Tabriz population in the future and two linear and quadratic equations are introduced for water consumption demand. Also, this study indicated that Tabriz's population growth rate followed on an exponential model from 1956 to 1975. Nevertheless, from 1976, later for various reasons, the population growth pattern turned out to be a logistics function model. In addition, by using this method, it is possible to better plan for the future of this city in terms of water scarcity, water demand and consumption, and water security. The used method can be applied to other cities and regions to predict the population numbers and to assess water scarcity.